Kikuchi-Fujimoto's disease associated with systemic lupus erythematous: difficult case report and literature review. (August 2014) - Ruaro, B; Sulli, A; Alessandri, E; Fraternali-Orcioni, G; Cutolo, M
Kikuchi–Fujimoto's disease (KFD), or histiocytic necrotizing lymphadenitis, is a benign and self-limiting disease of unknown aetiology. KFD tends to affect a young population under 30 years of age and predominantly females. KFD is a rare pathology and its association with systemic lupus erythematosus (SLE) is not frequent. Herein, we present the case of a male Italian patient with SLE in association with KFD with 5 years of follow-up, where a differential diagnosis from infection or lymphoproliferative disease was problematic.